Differences in subependymal vein anatomy may predispose preterm infants to GMH–IVH. Issue 1 (6th June 2017) - Tortora, Domenico; Severino, Mariasavina; Malova, Mariya; Parodi, Alessandro; Morana, Giovanni; Sedlacik, Jan; Govaert, Paul; Volpe, Joseph J; Rossi, Andrea; Ramenghi, Luca Antonio
Abstract : Background and purpose: The anatomy of the deep venous system plays an important role in the pathogenesis of brain lesions in the preterm brain as shown by different histological studies. The aims of this study were to compare the subependymal vein anatomy of preterm neonates with germinal matrix haemorrhage–intraventricular haemorrhage (GMH–IVH), as evaluated by susceptibility-weighted imaging (SWI) venography, with a group of age-matched controls with normal brain MRI, and to explore the relationship between the anatomical features of subependymal veins and clinical risk factors for GMH–IVH. Methods: SWI venographies of 48 neonates with GMH–IVH and 130 neonates with normal brain MRI were retrospectively evaluated. Subependymal vein anatomy was classified into six different patterns: type 1 represented the classic pattern and types 2–6 were considered anatomic variants. A quantitative analysis of the venous curvature index was performed. Variables were analysed by using Mann-Whitney U and χ 2 tests, and a multiple logistic regression analysis was performed to evaluate the association between anatomical features, clinical factors and GMH–IVH. Results: A significant difference was noticed among the six anatomical patterns according to the presence of GMH–IVH (χ 2 =14.242, p=0.014). Anatomic variants were observed with higher frequency in neonates with GMH–IVH than in controls (62.2% and 49.6%, respectively). Neonates with GMH–IVH presented a narrower curvature of the terminal portion of subependymal veins (p<0.05). These anatomical features were significantly associated with GMH–IVH (p<0.05). Conclusion: Preterm neonates with GMH–IVH show higher variability of subependymal veins anatomy confirming a potential role as predisposing factor for GMH–IVH.